Interaction between the lateral preoptic area and the subfornical organ in the control of water ingestion caused by cellular dehydration, hypotension, hypovolemia, and deprivation - Abrao Saad, W.; Antonio de Arruda Camargo, L. (My University, 1980)
Water intake was studied in albino rats with lesions in the lateral preoptic area, in the subfornical organ, and in both the lateral preoptic area and the subfornical organ. Drinking was induced by cellular dehydration, hypovolemia, hypotension (isoproterenol or caval ligation), and water deprivation. The animals with lesions in both areas showed a significant reduction in their water intake in response to cellular dehydration. Drinking due to extracellular dehydration was reduced in the animals that received only subfornical organ lesions, and was reduced even further in the animals with both areas ablated. The lesions in the subfornical organ were sufficient to reduce the thirst induced by caval ligation. The lesions in both areas inhibit water intake induced by caval ligation. Water intake induced by deprivation was reduced when both areas were destroyed. These findings demonstrate that both the lateral preoptic area and the subfornical organ are necessary for normal drinking in response to cellular dehydration, hypovolemia, and hypotension. There is further evidence that the lateral preoptic area and subfornical organ interact in the control of water intake induced by a variety of thirst challenges.
Keywords: animal experiment; blood and hemopoietic system; brain injury; cardiovascular system; central nervous system; dehydration; drinking; hypotension; hypovolemia; preoptic area; rat; subfornical organ; Animal; Blood Pressure; Blood Volume; Drinking; Extracellular Space; Hypothalamus; Intracellular Fluid; Male; Neural Pathways; Neurosecretory Systems; Preoptic Area; Rats; Subfornical Organ; Support, U.S. Gov't, P.H.S.; Water Deprivation; Water-Electrolyte Balance